E-democracy and social networks in Ecuador. A survey on the municipal elections 2014 (2017)
Social networks, among other possibilities, offer election protagonists the opportunity to direct a message to multitudes of individuals. Through an effective use of this medium, it is possible to generate the enormous advantage of amplifying the assimilation and response ca pacity in a potentially overwhelming manner. In this article, a survey is conducted geared toward quantifying the opinions of a group of Ecuadorian citizens regarding the impact of social networks on municipal elections held in that country in February, 2014. The main results show a lack of dialogue between candidates and citizens, indications that underscore the lack of a culture of political participation, replicated through the cyber sphere, and the existence of some informational content anchored to offline routines.